Monitoring the interfacial electric field in pure and doped SrTiO3 surfaces by means of phase-resolved optical second harmonic generation. (May 2018) - Rubano, Andrea; Mou, Sen; Paparo, Domenico
Highlights: A new technique for monitoring the growth of functional oxides thin films is proposed. It is based on phase-resolved optical second harmonic generation. It measures the amplitude and phase of the interfacial electric field. It has been proved to work ex-situ on Nb-doped and undoped strontium titanate. Abstract: Oxides and new functional materials such as oxide-based hetero-structures are very good candidates to achieve the goal of the next generation electronics. One of the main features that rules the electronic behavior of these compounds is the interfacial electric field which confines the charge carriers to a quasi-two-dimensional space region. The sign of the confined charge clearly depends on the electric field direction, which is however a very elusive quantity, as most techniques can only detect its absolute value. Even more valuable would be to access the sign of the interfacial electric field directly during the sample growth, being thus able to optimize the growth conditions directly looking at the feature of interest. For this aim, solid and reliable sensors are needed for monitoring the thin films while grown. Recently optical second harmonic generation has been proposed by us as a tool for non-invasive, non-destructive, real-time, in-situ imaging of oxide epitaxial film growth. The spatial resolution of this technique has been exploited to obtain real-time images of the sample under investigation. Here we propose to exploit another very important physical property of the second harmonic wave: its phase, which is directly coupled with the electric field direction, as shown by our measurements.